Darier's disease in Slovenia - Miljković, Jovan (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2000)
Background. Dyskeratosis follicularis (Darier-White, morbus Darier, MD) is an autosomal dominant skin disorder characterized by warty papules and plaques primarily in seborrheic areas, palmo-plantar pits and nail abnormalities. Our purpose was to collect the information on the prevalence of patients affected with MD in Slovenia. Materials and methods. Records from Departments of dermatology in Slovenia were studied and new cases were registered. Clinical symptoms and other relevant data from 27 patients who had followed our invitation for a re-examination were collected in special questionnaires. Results. Altogether 44 patients were recorded, 20 were males and 24 females. Taking into account that the Slovenian population amounts to roughly 2 million, this would give a prevalence of 2.2/100 000. Altogether 27 patients followed the invitation for a re-examination. Greasy papules were expressed inall the patients, nail involvement ranked second with 89%. Trunk and limbs were involved in 89% of patients and the face in 89%. The onset of the diseasewas in the majority of cases in the second decade of life, in all patients the symptoms appeared before the age of forty. Conclusion. The prevalence of this condition is similar to that in England, Denmark and Croatia.
Keywords: Age of onset; dermatologija; Diagnosis; diagnostika; Epidemiology; Keratosis follicularis; kožne bolezni; Pedigree